Investigation of Water Resources-Related Legal Violations Following Constitutional Court Decision Number 85/PUU-XI/2013 - Martini; Absi, Warmiyana Zaira (LITIGASI, 2025)
This study was conducted to analyze legal violations related to water resources after the Constitutional Court's decision to annul Law No. 7 of 2004 concerning Water Resources. The decision caused confusion regarding the legal position of Civil Servant Investigators for Water Resources (PPNS SDA) in enforcing the law related to air resource management. The purpose of this study is to explore the legal status of PPNS SDA after regulatory changes and to assess the challenges faced in investigating legal violations in the air resource sector. The research method used in the analysis is qualitative, which includes literature studies from various legal sources, scientific articles, and interviews with relevant stakeholders in water resource management and protection. The results of the study indicate that despite the existence of laws and regulations, PPNS SDA are still legally recognized and have certain authorities in examining and investigating alleged violations of the law related to water resources. This study also identified several cases of investigations carried out by PPNS SDA, as well as coordination with other law enforcement officers. From the results of the study, it can be concluded that PPNS SDA still have legal standing in conducting investigations related to water resources despite regulatory changes. The investigation procedures followed by PPNS SDA are in accordance with the established methodology, but still require ongoing collaboration with other agencies, such as the police and prosecutors.